Strategi Pengembangan Usaha Budidaya Udang Vannamei Dalam Meningkatkan Pendapatan Petambak di Kecamatan Klirong Kabupaten Kebumen - Siti Mazidatul Qonita; Joko Purwono; Feryanto Feryanto (Jurnal Agribisnis Indonesia, 2024)
Vannamei shrimp is a fishery commodity that has the potential to be developed. Klirong District has a high volume and value of vannamei shrimp production in Kebumen Regency. This research aims to analyze the vannamei shrimp commodity base, classify the growth of vannamei shrimp cultivation businesses, and formulate appropriate development strategies for vannamei shrimp cultivation businesses in Klirong District, Kebumen Regency. This research will analyze several aspects, including Location Quotient (LQ) analysis, Klassen Matrix analysis, External and Internal Factors, SWOT analysis, and formulating alternative strategies using the QSPM matrix. This research shows that vannamei shrimp is an essential commodity in Klirong District, Kebumen Regency, with a value of 1.18. Vannamie shrimp commodities in Klirong District, Kebumen Regency, are classified as advanced and slow-growing commodities. There are twelve alternative strategies in developing the vannamei shrimp cultivation business, the three strategic priorities with the highest value include implementing environmentally sound farming business practices, adopting innovative technology and implementing digitalization in production and marketing systems, as well as establishing good relationships with suppliers and customers and also expanding marketing.